KEBIJAKAN KEPALA SEKOLAH DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SMA NEGERI 3 TUNGKAL JAYA - Veronika Siti Agustin; Salahuddin Salahuddin; Atika Atika (STKIP Pesisir Selatan, 2026)
This study is motivated by the importance of developing students’ disciplinary character in education, which is influenced by the principal’s policies. At SMA Negeri 3 Tungkal Jaya, efforts to build students’ discipline have been implemented; however, they have not been carried out optimally. Various violations are still found, such as tardiness, lack of neatness, and low awareness of school rules. Therefore, this study aims to identify the principal’s policies, the types of violations that occur, and the obstacles in developing students’ disciplinary character. This study uses a qualitative approach with a field research design. The research was conducted at SMA Negeri 3 Tungkal Jaya, Musi Banyuasin Regency. The research subjects include the principal, vice principal, teachers, and students. Data were collected through interviews, observations, and documentation. The collected data were then analyzed descriptively to describe the actual conditions related to the principal’s policies in shaping students’ disciplinary character. The results show that the principal’s policies in developing students’ disciplinary character have been implemented through school rules, sanctions, and habituation of disciplined activities. However, the implementation has not been optimal due to several obstacles, such as differences in students’ backgrounds, environmental and social media influences, and the lack of parental support and supervision. These factors cause the development of students’ disciplinary character to not yet be fully achieved optimally.